Manajemen Operasional Hotel Syariah Menurut Maqashid Syariah Di Indonesia - Ghulam Asy Sya’Bany; Wisnu Handika Adi Cahyo; Ummu Karomah; Hikmatus Sa’diyah; Eny Latifah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to examine the implementation of Maqashid Syariah in sharia hotel operational management. Maqashid Syariah, which includes the main objectives of sharia such as the protection of religion, soul, mind, lineage and property, is the main basis for managing sharia hotels. With a qualitative approach, this research analyzes various aspects of operational management, including guest service, human resource management, financial policies, and hygiene and security practices. The research results show that the application of Maqashid Syariah principles in hotel operations not only ensures compliance with Islamic law but also improves service quality and customer satisfaction. The implementation of sharia values ​​in every aspect of operational management contributes to the creation of a harmonious and sustainable environment, as well as strengthening the position of sharia hotels in the competitive hotel industry. This study suggests that sharia hotel managers continue to integrate Maqashid Syariah principles to achieve sustainability and operational excellence.